THE INFLUENCE OF RETURN ON ASSETS AND LIQUIDITY ON STOCK PRICES OF TECHNOLOGY SECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE PERIOD 2016-2020 - Iskandar Zulkarnain; Azimah Hanifah; Gatot Nazir Ahmad (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
Analysis of the Effect of Return on Assets and Liquidity on stock prices of Technology sector companies on the Indonesian Stock Exchange for the 2016-2020 period research objectives (1) To determine the effect of Return on Assets on stock prices of technology sector companies on the Indonesia Stock Exchange for the 2016-2020 period. (2) To determine the effect of liquidity on the stock prices of technology sector companies on the Indonesia Stock Exchange for the 2016-2020 period. (3) To determine the effect of Return on Assets and Liquidity on the stock prices of technology sector companies on the Indonesia Stock Exchange for the 2016-2020 period. The research method uses multiple regression with a sample size of 7 technology sector companies Research results (1) There is a positive and significant influence between Return on Assets (ROA) on the stock prices of technology sector companies on the Indonesia Stock Exchange for the period 2016 - 2020. (2) There is no influence on Liquidity, on the stock prices of technology sector companies on the Indonesia Stock Exchange for the period 2016 – 2020. (3) 3. There is an influenceReturn On Asset (ROA) and Liquidity together on Technology stock prices on the Indonesia Stock Exchange for the 2016 – 2020 period.